2020
DOI: 10.21082/fae.v38n1.2020.29-52
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Upsus Program on the Cost Efficiency and Competitiveness of Rice Production in Indonesia

Abstract: <p>Program Upsus adalah program nasional yang dirintis pada tahun 2014 dan mulai diterapkan secara besar-besaran pada tahun 2015. Dalam program ini, padi mendapatkan porsi terbesar dari anggaran pemerintah, dan diharapkan dapat meningkatkan produksi beras melalui peningkatan luas areal panen dan produktivitas. Target yang ditetapkan adalah bahwa Indonesia akan mencapai swasembada beras lagi dalam tiga tahun. Setelah itu, targetnya adalah Indonesia dapat memelihara keberlanjutan swasembada beras, mencapai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
0
0
Order By: Relevance
“…This indicated that public understanding of the program still needs to be improved; this condition will almost certainly result in less than the maximum program acceptance and achievement level. Another study discovered that farmers needed to learn about the UPSUS Pajele program (Setiyanto, 2021; Setiyanto & Pabuayon, 2020) (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…This indicated that public understanding of the program still needs to be improved; this condition will almost certainly result in less than the maximum program acceptance and achievement level. Another study discovered that farmers needed to learn about the UPSUS Pajele program (Setiyanto, 2021; Setiyanto & Pabuayon, 2020) (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…Analyzing the technical efficiency using stochastic frontier analysis (SFA) is somehow still a popular and reliable calculation of the efficiency level and factors that influence inefficiency. To the authors' knowledge, in Indonesia, there are only a few empirically based studies evaluated the impact of the Upsus Pajale program [11,[25][26][27][28][29]. Most of those studies analyzed the factors that influence the inefficiency using characteristic demographics and social economics of farmers' household [18,[30][31][32].…”
Section: Introductionmentioning
confidence: 99%